Cost Competitively Design Elements At Pegasus' Zortman-Landusky Gold Operations - A Case History - Michael L. Clark; Carson Rife (Society for Mining, Metallurgy & Exploration, 1987)
INTRODUCTION Zortman Mining Inc. is a wholly owned subsidiary of Pegasus Gold Corporation of Spokane, Washington. Pegasus has been producing gold and silver from the Zortman and Landusky mines since 1979. The Zortman and Landusky mines are two distinct open pit mines located approximately 6 kilometers apart in the Little Rockies Mining District of north central Montana. The two mines use large-tonnage, low- grade heap leaching techniques to efficiently process the gold and silver ore. PROJECT DESCRIPTION The Little Rockies rise abruptly 914 metres from the surrounding plains to about 1829 metres above sea level. The topography is quite steep, making efficient leach pad construction a major challenge. The climate is semi-arid with moderate summers and occasionally severe winters. Freezing temperatures usually arrive in late October or early November, influencing the effectiveness of leaching operations. GEOLOGY AND MINERALOGY The geology of the Little Rocky Mountains consists of steeply dipping sedimentary ridges forming an elliptical dome surrounding a core of intruding syenite porphyry. Within the syenite porphyry are well fractured and mineralized shear zones where the existing reserves and open pits are located. The ore is presently divided into oxidized, mixed, and sulfide. Only the oxides and mixed zones that are of ore grade are placed on the leach pads. The syenite porphyry host rock enables effective leaching of gold and silver to depths of 61 metres, having a major impact on leach pad construction costs. MINING All mining since 1979 has been by contractor. This enabled initial mining to commence without capital investment in equipment. Through competitive negotiations, Pegasus has been able to keep contract mining costs at levels very close to what would be experienced if Pegasus had purchased equipment initially. Contracts are negotiated yearly and are based on a unit price and haul distance for ore and waste. Haul distances have ranged from as little as 457 metres to as much as 3,050 metres. At present, Pegasus is developing a 27,000,000-tonne leach pad at the Landusky project that is adjacent to the minine area. This design feature will reduce the mining cost by 20 percent over the life of the mine. In 1987, over 5,900,000 tonnes of ore and 3,200,000 tonnes of waste will be mined at the Landusky project. Through 1986, 13,763,000 tonnes of ore have been mined at a waste-to-ore strip ratio of 0.60:l at the Zortman project, and 13,005,000 tonnes of ore at a waste-to-ore strip ratio of 0.79:l have been mined at the Landusky project. Current mining reserves are 32,769,000 tonnes of ore at a waste- to-ore strip ratio of 0.59:l. Through efficiencies of large-scale heap leaching, Pegasus has been able to lower the mining cutoff from 0.34 grams per tonne gold to 0.27 grams per tonne gold. This has reduced the mining cost per tonne of ore h percent through a reduction in strip ratio of 14 percent. Beginning in 1984, all pits were designed based on computer-generated "floating cone" pits. The geologic models were developed by Pegasus staff with a series of economic models evaluated. The resulting computer-generated pits were used as a guideline in designing the mine plans, including haul roads for final calculation of tons and grade. Input to the floating cone models consisted of mining cost, processing cost, cutoff grade (0.34 grams gold per tonne), recovery (67 percent) and gold price. Due to the gold being deposited primarily on the fractures of the syenite host rock, no crushing of ore is needed prior to leaching. This characteristic of the ore is a key in being able to profitably mine and process gold ore at an average grade of 0.69 grams of gold per tonne. Strict blasting control is also a key in success of the leaching operation. A system of splitting ore and waste in blast patterns has been devised to reduce dilution. Also, drill hole spacings are varied from 3m x 3m in breccia ore to 4m x 4m in syenite ore to 5m x 5m in waste. Drill holes